UJI BIOAKTIFITAS ANTIBAKTERI EKSTRAK DAN FRAKSI DARI DAUN PULAI (Alstonia scholaris) TERHADAP Staphylococcus aureu (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Staphylococcus aureus is the normal microflora of the human body. These bacteria can turn into pathogens from migrating to other areas of the body, the wounds and lower the body's immune system causes ulcers, blood clots and other. One way to overcome this is by using pulai leaf. The porfuse research is to determine the bioactive material and antibacterial compounds contained in the pulai leaves bioaktifitasnya tested against S. aureus bacteria. Experimental research has been conducted on the antibacterial compound isolation process is done in a way: using Soxhlet extraction, fractionation using vacuum liquid chromatography, and purification by column chromatography gravity. Antibacterial bioactivity testing performed by the agar diffusion method. The results showed that the pulai leaves have antibacterial ability against S. aureus. The most active extract is methanol. Active fraction contained in the pulai leavesÂ  belonged phenolic compounds.Â Keywords: antibacterial bioactivity, extract, fractions, pulai leaves, Staphylococcus aureus.